EXPLORING PRE-SERVICE ENGLISH TEACHERS' DEMOTIVATION IN ESSAY WRITING CLASS - Noor Muthi'ah; Luqman Baehaqi; Zaitun Qamariah; Tawfiq Sarehmansor (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the phenomenon of demotivation in essay writing among pre-service English teachers at UIN Palangka Raya. Academic writing is often perceived as difficult by EFL learners due to limited vocabulary, weak grammar, and challenges in organizing ideas, which reduce students’ confidence (Baehaqi, 2023). Moreover, even teachers tend to avoid academic writing because of insufficient knowledge and low confidence (Qamariah et al., 2023). Using a qualitative phenomenological design (Moustakas, 1994), data were collected through semi-structured interviews with ten students who had completed essay writing courses and analyzed through epoche, phenomenological reduction, imaginative variation, and synthesis of meanings and essences. The findings revealed seven themes of demotivation: language-related anxiety, unclear instruction and passive teaching style, loss of autonomy and relevance gap, time pressure and preparation gap, class format and timing issues, coping strategies, and supportive teaching as motivator. Both internal and external factors contributed to demotivation, yet students managed to cope through peer collaboration, self-regulation, and online resources, while supportive teaching emerged as a key factor in restoring motivation. This study contributes to the understanding of demotivation in EFL essay writing and underscores the importance of empathetic, autonomy-supportive, and process-oriented teaching practices in sustaining student engagemen.